Influence of Pre-Training Predator Stress on the Expression of c-fos mRNA in the Hippocampus, Amygdala, and Striatum Following Long-Term Spatial Memory Retrieval - VanElzakker, Michael B.; Zoladz, Phillip R.; Thompson, Vanessa M.; Park, Collin R.; Halonen, Joshua D.; Spencer, Robert L.; Diamond, David M. (Frontiers in Behavioral Neuroscience, 2011)
We have studied the influence of pre-training psychological stress on the expression of c-fos mRNA following long-term spatial memory retrieval. Rats were trained to learn the location of a hidden escape platform in the radial-arm water maze, and then their memory for the platform location was assessed 24 hr later. Rat brains were extracted 30 min after the 24 hr memory test trial for analysis of c-fos mRNA. Four groups were tested: 1) Rats given standard training (Standard); 2) Rats given cat exposure (Predator Stress) 30 min prior to training (Pre-Training Stress); 3) Rats given water exposure only (Water Yoked); and 4) Rats given no water exposure (Home Cage). The Standard trained group exhibited excellent 24 hr memory which was accompanied by increased c-fos mRNA in the dorsal hippocampus and basolateral amygdala (BLA). The Water Yoked group exhibited no increase in c-fos mRNA in any brain region. Rats in the Pre-Training Stress group were classified into two subgroups: good and bad memory performers. Neither of the two Pre-Training Stress subgroups exhibited a significant change in c-fos mRNA expression in the dorsal hippocampus or BLA. Instead, stressed rats with good memory exhibited significantly greater c-fos mRNA expression in the dorsolateral striatum (DLS) compared to stressed rats with bad memory. This finding suggests that stressed rats with good memory used their DLS to generate a non-spatial (cue-based) strategy to learn and subsequently retrieve the memory of the platform location. Collectively, these findings provide evidence at a molecular level for the involvement of the hippocampus and BLA in the retrieval of spatial memory and contribute novel observations on the influence of pre-training stress in activating the DLS in response to long-term memory retrieval.